1996
DOI: 10.1017/s0022215100132773
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent laryngeal papillomatosis developing into laryngeal carcinoma with human papilloma virus (HPV) type 18: a case report

Abstract: We report a case of recurrent laryngeal papillomatosis which developed into laryngeal squamous cell carcinoma 11 years after the first diagnosis. Interestingly, we could identify HPV type 18 DNA in the carcinoma tissue using the polymerase chain reaction (PCR). Other known risk factors of irradiation, smoking, exposure to chemical agents, or a hereditary tendency to malignant tumours were not present in this case. Our finding suggests that HPV type 18 is another aetiological agent for laryngeal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…This procedure is prone to aerosolization of virus and may not be the optimal technique for isolating large quantities of virus. HPVs are potential oncogenic pathogens and genital HPVs have been detected in laryngeal papillomas and carcinomas (Atula et al ., 1999 ; Dickens et al ., 1991 ; Moore et al ., 1999 ; Sakakura et al ., 1996 ). Therefore, we sought to develop an efficient approach for extracting HPV virions that was more biologically contained and that reduced aerosolization of this human pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…This procedure is prone to aerosolization of virus and may not be the optimal technique for isolating large quantities of virus. HPVs are potential oncogenic pathogens and genital HPVs have been detected in laryngeal papillomas and carcinomas (Atula et al ., 1999 ; Dickens et al ., 1991 ; Moore et al ., 1999 ; Sakakura et al ., 1996 ). Therefore, we sought to develop an efficient approach for extracting HPV virions that was more biologically contained and that reduced aerosolization of this human pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…HPV typing was performed in two cases of malignant transformation of adult-onset laryngeal papillomatosis. In these cases, squamous cell carcinomas of the larynx were found to be associated with HPV 6 (18) or HPV 18 (20). Review of the literature shows no reported cases of malignant change of a pulmonary papilloma in the setting of adult-onset papillomatosis.…”
Section: Discussionmentioning
confidence: 98%
“…Additional reports note that HPV 11 is most frequently followed by malignant transformation, followed by HPV 16/18. [15,16] Furthermore, protein expression of p53, pRb, p21, and p16 in recurrent respiratory papillomatosis has also been reported. Lele studied four cases of juvenile-onset recurrent respiratory papillomatosis progressing to carcinoma in which HPV 11 was the only human papillomavirus type identified in all cases.…”
Section: Discussionmentioning
confidence: 96%